Study of structure, base-pair opening kinetics and proton exchange mechanism of the d-(AATTGCAATT) self-complementary oligodeoxynucleotide in solution. - Kochoyan, M (1988)
Using proton magnetic resonance, we have investigated the structure and the base-pair opening kinetics of the d-(AATTGCAATT) self-complementary duplex. All the non-exchangeable (except H5',5") and most exchangeable proton resonances have been assigned. The structure belongs to the B family. Imino proton exchange, measured by line broadening, longitudinal relaxation and magnetization transfer from water, is catalyzed by proton acceptors. The base-pair lifetimes, obtained by extrapolation of the exchange times to infinite concentration of ammonia are 2 and 3 milliseconds for internal A.Ts and 18 ms for G.C at 15 degrees C. In the absence of added catalysts, the imino proton of the first A.T base pair exchanges faster than that of the unpaired thymidine of the duplex formed by the sequence d-(AATTGCAATTT). This gives strong evidence for intrinsic exchange catalysis. The exchange of adenine amino protons from the closed state has been observed. Hence amino proton exchange is ill-suited for the investigation of base-pair opening kinetics.